Nigeria : State Finances Study - World Bank (Washington, DC, 2013)
Fiscal management and broader macroeconomic policy is complicated when government financing is highly dependent on natural resource revenues and therefore susceptible to wide fluctuations. This challenge is compounded further in a context of fiscal federalism, particularly when sub national governments have considerable autonomy over their spending, constitute a significant share of consolidated government financing and lack a tradition of strong fiscal discipline. Nigeria happens to be in this situation: government is highly dependent on oil revenues and inappropriate management of the oil revenue cycle has historically been at the heart of macroeconomic instability in the country. In recent years, Nigeria's new fiscal federalism context and the increased autonomy of states, has added additional challenges to the conduct of fiscal and macroeconomic policy. Nigeria is a federation with power and responsibilities shared between the Federal Government and thirty-six constituent state governments' Local governments are constitutionally recognized but are subject to the creation, control and regulation of State governments. As in similar federal structures, the power and ability of state governments to manage their public expenditure depend largely on the fiscal federalism arrangements in place. It is necessary therefore to begin this report on States Finances by examining how fiscal powers and responsibilities are shared between the various levels of government and what mechanisms are in place for securing synergy and avoiding dysfunction(Chapter 1). This chapter describes the nature of the Nigerian federation. This is followed by a discussion of revenue assignments for funding the various levels of government. This will be closely tied with the arrangements for sharing common revenues, a very important feature of Nigeria's fiscal federalism. Section D discusses expenditure assignments. The concluding section of Chapter 1 briefly discusses key implications of the April 2002 Supreme Court ruling on certain aspects of Fiscal Federalism in Nigeria. Chapter 2 reviews the states' finances from 1997 through 2001. This chapter concludes that In the medium term, states' will need to vigorously address the structural constraints to their improved fiscal Performance. This will require specific actions to: (i) build a tradition of strong fiscal discipline; (ii) reduce and manage states' vulnerability to o i l price swings; (iii) reduce the share of inflexible commitments in states' expenditure profiles; (iv) promote prudent borrowing and debt; and (v) strengthen budget processes and institutions to support fiscal discipline and expenditure efficiency and effectiveness. The discussion in Chapters 3 and 4 lay out some concrete proposals for the consideration of state and federal governments. More specifically, Chapter 3 discusses aspects of current fiscal federalism arrangements including arrangements for borrowing that might encourage imprudent or fiscally irresponsible behavior by Nigerian states. It also examines mechanisms that could be used to harden budget constraints and promote the fiscal discipline needed for overall macroeconomic stability and for efficient use of states' public resources. Actions will be needed at both state and federal government levels, with the latter playing a lead role, including through demonstrating a credible commitment to fiscal discipline. Finally, Chapter 4 reviews budget and financial management practices in Nigerian states, identifies areas of weaknesses and proposes key elements of these process and institutional reforms.